Long Term Outcome of 112 Pediatric Patients With Ureteroplevic Junction Obstruction Treated by Endourologic Retrograde Balloon Dilatation - Ordóñez, Javier; Ortiz, Rubén; Parente, Alberto; Burgos, Laura; Fernández-Bautista, Beatriz; Pérez-Egido, Laura; Angulo, José María (Frontiers in Pediatrics, 2022)
Purpose: To analyze the effectiveness, complications and long-term outcome of the patients with ureteropelvic junction obstruction (UPJO) treated by endoscopic retrograde balloon dilatation (ERBD) in the largest series reported. Materials and methods: Between years 2004 and 2018, 112 patients with primary unilateral UPJO were treated by ERBD. Endoscopic treatment consisted on a retrograde balloon dilatation of the ureteropelvic junction (UPJ), through cystoscopy and under fluoroscopic guidance, using high-pressure balloon catheters. In case of persistence in the balloon notch, a Cutting Balloon™ catheter was used. Double-J stent was placed after dilatation. Results: Mean age at surgery was 13.1 +/- 21.3 months, 92 cases being younger than 18 months. Mean operative time was 24.4 +/- 10.3 minutes; hospital stay was 1 day in 82% of patients. No intraoperative complications occurred. UPJ was calibrated at time of stent removal with cystoscopy 39.1 +/- 13.7 days after dilatation. ERBD was not possible in 11 cases. An additional procedure was needed in 24 cases: second ERBD (n=11, 7 during the stent withdrawal), a third dilatation (n=3) due to persistent hydronephrosis, and percutaneous endopyelotomy (n=3) or open pyeloplasty (n=7) in cases of technical failure. Significant improvement in postoperative ultrasound measures were observed (p<0.05, T-test). Long-term success rate was 76.8% after one dilatation, and 86.6% in those who required up to 2 dilatations. Mean follow-up was 66.7 +/- 37.5 months. Conclusions: ERBD is a feasible and safe option for the minimally invasive treatment of UPJ obstruction in infants. Long-term outcome is acceptable with a very low complication rate.